Durabilidade de concretos com adição de sílica da casca de arroz à penetração de íons cloretos - Mendes, Gabriel Gavião (2014)
The chloride ions are the principals initiators agents of corrosion of armors in reinforced concrete structures, this happened due his capacity of destroy the passivation film generated for the Portland concrete (Neville, 1997). The objective this work is studies the effects of the addition of silica from rice husk, obtained by burn in layer fluidized, in the durability of concrete, based Portland cement of kind CPII-Z, front of penetration of chloride ions. In this work were analyzed, beyond of mixture reference, another three mixtures, what was substituted the Portland cement for silica from rice husk, in the levels of 3%, 5% and 10%. For the evaluation of durability this concretes of penetration chloride ions were adopted two methods: accelerated test of penetration of chloride ions, and the test of penetration of chloride ions for immersion in saline. Also were realized resistance tests for axial compression to analysis of mechanic comportment of studied concretes. The tests were realized to 56 days and to 91 years old. The samples from of silica from rice husk mixtures presented a reduction of average deepness of the penetration of chloride ions and of passing load, being that the mixture containing 5% of silica was that showed the best results, reducing in approximately 25% of the value the passing load in the accelerate test, realized to 91 days. The average depth of penetration of chlorides in the immersion tests was approximately 37% lower for the blend containing 5% silica rice husk compared to the reference mixture.